"Science is Everywhere, but No One Knows It": Assessing the Cultural Distance to Science of Rural South African Publics. Issue 8 (17th November 2018) - Guenther, Lars; Weingart, Peter; Meyer, Corlia
ABSTRACT: In science communication, a prerequisite for reaching different parts of a society is to find out how these publics experience and interpret science. Since rural South African publics are perceived to exhibit a large cultural distance to science, the present exploratory study aimed to know in more detail how rural South Africans perceive and understand science in their local and social contexts. Theoretical notions on cultural distance and the methodological approach of segmentation studies were considered. Semi-structured interviews with rural South Africans were carried out in four towns ( n  = 52) that differ with respect to having a large scientific installation in their vicinity, or not. Sensitively comparing local and social contexts helped identifying three different publics who differed regarding their perceptions of science; however, the large scientific installations only made a difference in perceptions for those publics who were generally less exposed to and less knowledgeable about science.